Comparison of plastic and glass cages on volatile compounds in protein extracted from Protaetia brevitarsis larvae - Ji Yoon Cha; Tae-Kyung Kim; Yea-Ji Kim; Jae-Hoon Lee; Min-Cheol Kang; Hae Won Jang; Yun-Sang Choi (Future Foods)
Edible insects, known for their high-protein production efficiency, are vital for enhancing food security. However, standardized breeding protocols are lacking, and research on the impact of cage materials on insect product composition is limited. This study investigated the volatile compounds and processing properties of protein from Protaetia brevitarsis larvae reared in plastic and glass cages. Protein extracts from larvae reared in plastic cages contained 14 types of hydrocarbons, 4 types of ketones, and 1 type of phenol. Those reared in glass cages contained two types of acids, seven types of alcohols, and five types of aldehydes. Notably, plastic-derived compounds, such as p-xylene (110.87 μg/mL) and o-xylene (37.98 μg/mL), were significantly higher in the extracts from plastic cages, indicating potential plastic exposure. Processing properties, including protein solubility, pH, color, foaming properties, and emulsion characteristics, showed no significant differences between the two rearing conditions (P > 0.05). Therefore, considering the detection and potential accumulation of plastic-derived volatile compounds, using glass cages may be more beneficial for rearing insects for protein production.